2007
DOI: 10.1007/s00330-007-0670-6
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance cholangiography: comparison of two- and three-dimensional sequences for assessment of malignant biliary obstruction

Abstract: The purpose was to retrospectively compare two-dimensional (2D) magnetic resonance cholangiography (MRC) including breath-hold single-shot rapid acquisition with relaxation enhancement (RARE) and multislice half-Fourier RARE versus navigator-triggered 3D-RARE MRC in the evaluation of biliary malignancy. MRC findings were evaluated in 31 patients with malignant biliary obstruction, including biliary malignancy, gallbladder carcinoma, and ampullary cancer. Two observers independently reviewed the images to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 25 publications
1
16
0
1
Order By: Relevance
“…MRI with MRCP represents one of the most comprehensive imaging examinations currently available for evaluating periampullary obstruction. MRCP can outline the morphology of the bile and pancreatic ducts, and conventional MRI may improve the specificity of MRCP by allowing observation of periductal masses and pancreatic parenchymal abnormalities [8,9,20]. An earlier study suggested that MRI combined with MRCP was a more accurate technique than CT in differentiating between malignant and benign lesions in patients with suspected periampullary tumours.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…MRI with MRCP represents one of the most comprehensive imaging examinations currently available for evaluating periampullary obstruction. MRCP can outline the morphology of the bile and pancreatic ducts, and conventional MRI may improve the specificity of MRCP by allowing observation of periductal masses and pancreatic parenchymal abnormalities [8,9,20]. An earlier study suggested that MRI combined with MRCP was a more accurate technique than CT in differentiating between malignant and benign lesions in patients with suspected periampullary tumours.…”
Section: Discussionmentioning
confidence: 98%
“…For differentiating PHC from non-PHC, a similar 5-point scale was used: 1, definitely PHC; 2, probably PHC; 3, indeterminate; 4, probably non-PHC; and 5, definitely non-PHC. The reviewers were aware that for statistical analysis purposes, only grades≤2 were considered a correct benign or PHC diagnosis, grades≥4 represented a correct malignant or non-PHC diagnosis, grade 3 was considered to indicate an incorrect diagnosis [8,20].…”
Section: Image Analysismentioning
confidence: 99%
“…Parole chiave Colangiopancreatografia-RM · Malattia biliare extraepatica · Ecografia endoscopica Introduzione Nelle ultime due decadi si è assistito ad un notevole progresso nella diagnosi della patologia biliare e pancreatica, grazie allo sviluppo ed al successivo consolidamento della colangiopancreatografia con risonanza magnetica (CPRM), metodica diagnostica accurata e non invasiva nell'imaging biliare [1][2][3][4][5]. La CPRM è in grado di fornire una mappa anatomica completa ed affidabile dell'albero biliare, senza dover ricorrere all'utilizzo di radiazioni ionizzanti o alla somministrazione di mezzi di contrasto [6].…”
Section: Methodsunclassified
“…The last two decades have seen considerable progress in the diagnosis of biliary and pancreatic disease, thanks to the development and consolidation of magnetic resonance cholangiopancreatography (MRCP), an accurate and noninvasive diagnostic modality in biliary imaging [1][2][3][4][5]. MRCP is able to provide a complete and reliable anatomical map of the biliary tree without relying on ionising radiation or the use of contrast agents [6].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, 46 patients shows the typical features of CT and 42 patients shows the typical features of MRI were: (1) the dynamic nature of the enhanced feature of progressive nature of concentric enhancement, internal lesions was flaky, grid-like or liear strengthing; (2) intrahepatic duct dilatation; (3) capsular retraction; (4) satellite nodule is also seen. With the recent advances of imaging techniques, 3D MR cholangiopancreatography (3D-MRCP) is emerging as a promising technique due to its high image quality and ability to clarify anatomic relationships (Sodickson et al 2006;Glockner et al, 2007;Choi et al, 2008;Palmucci et al, 2010). The diagnostic procedures of IHHCC can be summarized as follows: clinical features 4 B-ultrasound 4 CT or MRI 4 surgical resection (radical resection or palliative resection or abdominal exploration) or stent implantation.…”
Section: Discussionmentioning
confidence: 99%